2014
DOI: 10.1021/jz501869f
|View full text |Cite
|
Sign up to set email alerts
|

Elusive Presence of Chloride in Mixed Halide Perovskite Solar Cells

Abstract: The role of chloride in the MAPbI3-xClx perovskite is still limitedly understood, albeit subjected of much debate. Here, we present a combined angle-resolved X-ray photoelectron spectroscopy (AR-XPS) and first-principles DFT modeling to investigate the MAPbI3-xClx/TiO2 interface. AR-XPS analyses carried out on ad hoc designed bilayers of MAPbI3-xClx perovskite deposited onto a flat TiO2 substrate reveal that the chloride is preferentially located in close proximity to the perovskite/TiO2 interface. DFT calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
198
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(221 citation statements)
references
References 37 publications
18
198
0
5
Order By: Relevance
“…[142] Additionally, they also suggested that the Cl − preferentially located at the interface of TiO 2 and PVSK. [143] In line with this discovery, recent reports also confirmed the inhomogeneous distribution of Cl − . [144][145][146][147] Combining hard X-ray photoelectron spectroscopy with fluorescence yield X-ray absorption spectroscopy, Starr [147] obtained a distribution map of Cl − .…”
Section: Cl/i Mixed Pvsksupporting
confidence: 56%
“…[142] Additionally, they also suggested that the Cl − preferentially located at the interface of TiO 2 and PVSK. [143] In line with this discovery, recent reports also confirmed the inhomogeneous distribution of Cl − . [144][145][146][147] Combining hard X-ray photoelectron spectroscopy with fluorescence yield X-ray absorption spectroscopy, Starr [147] obtained a distribution map of Cl − .…”
Section: Cl/i Mixed Pvsksupporting
confidence: 56%
“…[11,[60][61][62] Yet the exact role chloride actually plays has been rather puzzling: while earlier reports suggested doping effects [63] that could explain the longer charge carrier diffusion lengths, finding chloride in the final perovskite films has been rather challenging. [11,62,64,65] Chloride seems to have mainly an effect on the crystal growth, as was suspected previously, [11,63] and it has since been shown that it is released together with excess MA during film annealing, or, in general, that it can facilitate the release of excess organic compounds. [62,66] Binek et al [67] showed that MAPbCl 3 crystallizes directly after the deposition of the starting solution, thus acting as a template for the formation of the desired iodide-based perovskite via a slow halide exchange from the iodide-rich environment.…”
Section: Role Of Chloride Ionsmentioning
confidence: 99%
“…Therefore huge efforts have been devoted to the optimization of morphology and processing conditions, in particular by controlling the interactions of the material precursors in solution or with the substrate. [21][22][23][24][25] A further constraint factor in the spin-coated devices is that the number of layers allowed are limited by their solubility in orthogonal solvents. The fabrication of heterostructured devices may open ways to increase the number of layers allowing to decouple transport from optical characteristics, thus increasing the overall performances of the device, as already shown in small molecules based Organic LEDs (OLEDs).…”
Section: Doi: 101002/aelm201500325mentioning
confidence: 99%
“…It is well known in fact that mixed halide perovskites in which chloride atoms are present as doping agents are usually characterized by higher radiative deactivation yields. [ 7,21,34,37 ] Therefore, the future exploitation of such material could lead to vapor-processed Pero-LED with improved performances. Differently from OLEDs with standard molecular dyes, vapor-deposited Pero-LEDs do not exhibit any roll-off behavior also with a large density of injected carriers: radiative bi-molecular recombination becomes dominant over nonradiative recombination processes after the defects (shallow traps) are fi lled.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%